Anti-allergic, anti-inflammatory, and anti-hyperglycemic activity of Chasmanthe aethiopica leaf extract and its profiling using LC/MS and GLC/MS - Ayoub, Iriny; Korinek, Michal; El-Shazly, Mohamed; Wetterauer, Bernhard; El-Beshbishy, Hesham A.; Hwang, Tsong-Long; Chen, Bing-Hung; Chang, Fang-Rong; Wink, Michael; Singab, Abdel Nasser B.; Youssef, Fadia S. (Plants, 2021)
This study aims to comprehensively explore the phytoconstituents as well as investigate the different biological activities of Chasmanthe aethiopica (Iridaceae) for the first time. Metabolic profiling of the leaf methanol extract of C. aethiopica (CAL) was carried out using HPLC-PDA-ESI-MS/MS. Twenty-nine compounds were annotated belonging to various phytochemical classes including organic acids, cinnamic acid derivatives, flavonoids, isoflavonoids, and fatty acids. Myricetin-3-O-rhamnoside was the major compound identified. GLC/MS analysis of the n-hexane fraction (CAL-A) resulted in the identification of 45 compounds with palmitic acid (16.08%) and methyl hexadecanoic acid ester (11.91%) representing the major constituents. CAL-A exhibited a potent anti-allergic activity as evidenced by its potent inhibition of β-hexosaminidase release triggered by A23187 and IgE by 72.7% and 48.7%, respectively. Results were comparable to that of dexamethasone (10 nM) in the A23187 degranulation assay showing 80.7% inhibition for β-hexosaminidase release. Both the n-hexane (CAL-A) and dichloromethane (CAL-B) fractions exhibited potent anti-inflammatory activity manifested by the significant inhibition of superoxide anion generation and prohibition of elastase release. CAL showed anti-hyperglycemic activity in vivo using streptozotocin-induced diabetic rat model by reducing fasting blood glucose levels (FBG) by 53.44% as compared with STZ-treated rats along with a substantial increase in serum insulin by 22.22%. Molecular modeling studies indicated that dicaffeoylquinic acid showed the highest fitting with free binding energies (∆G) of −47.24 and −60.50 Kcal/mol for human α-amylase and α-glucosidase, respectively confirming its anti-hyperglycemic activity. Thus, C. aethiopica leaf extract could serve as an effective antioxidant natural remedy combating inflammation, allergy, and hyperglycemia.